2020
DOI: 10.1101/2020.02.27.968594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S1PR1 regulates the quiescence of lymphatic vessels by inhibiting laminar shear stress-dependent VEGF-C signaling

Abstract: During the growth of lymphatic vessels (lymphangiogenesis), lymphatic endothelial cells (LECs) at the growing front sprout by forming filopodia. Those tip cells are not exposed to circulating lymph, as they are not lumenized. In contrast, LECs that trail the growing front are exposed to shear stress, become quiescent and remodel into stable vessels. The mechanisms that coordinate the opposed activities of lymphatic sprouting and maturation remain poorly understood. Here we show that the canonical tip cell m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Lymphangiographies were performed as described on E17.5 embryos [15]. Briefly, 2 µL of 0.4% Trypan blue solution (Sigma) was injected into the dermis in periorbital region with a 36G beveled needle attached to a Nano l syringe (WPI).…”
Section: Lymphangiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphangiographies were performed as described on E17.5 embryos [15]. Briefly, 2 µL of 0.4% Trypan blue solution (Sigma) was injected into the dermis in periorbital region with a 36G beveled needle attached to a Nano l syringe (WPI).…”
Section: Lymphangiographymentioning
confidence: 99%
“…In embryonic dermal lymphangiogenesis, Notch1 deletion in LECs did not affect lymphatic branching, but increased lymphatic vessel caliber which was proposed to be secondary to an increase in LEC proliferation and decreased LEC apoptosis [14]. More recently, it was shown that loss of one copy of Dll4 was associated with reduced embryonic dermal lymphangiogenesis in mice [15], a phenotype opposite to that seen in retinal angiogenesis [7,8]. Additional studies are needed to clarify the differences in the lymphangiogenic phenotypes observed upon disruption of lymphatic endothelial Notch signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Although Notch signaling limits angiogenesis [69][70][71] , Notch has been reported to inhibit or augment lymphangiogenesis in a contextdependent fashion 38,39,72,73 . In addition, a recent study also documents the contrary role of two angiostatic components, DLL4 and S1PR1, in lymphangiogenesis 74 .…”
Section: Opposing Roles Of Aibp In Angiogenesis and Lymphangiogenesismentioning
confidence: 92%
“…Conversely, silencing or pharmacological blockade of S1PR1 resulted in increased RHOA-ROCK activity, junctional destabilization, and transient loss of junctional CLDN5. Consequently, junctional architecture and CLDN5 localization in S1PR1-silenced or inhibitor-treated LECs was restored by pharmacological inhibition of ROCK [54]. The peptide hormone adrenomedullin has also been implicated as an inhibitor of RHOA-ROCK activity under inflammatory conditions through protein kinase A (PKA) and Ras-related protein 1 (RAP1) signaling, thereby mediating junctional stabilization of dermal LECs [55].…”
Section: Open Accessmentioning
confidence: 99%
“…Laminar shear enhances proliferation and sprouting in cultured LECs via Notch inhibition as well as by activating Ca 2+ signaling and the flow-sensitive transcription factors Krüppel-like factor 2/4 (KLF2/4) [87,88]. Laminar shear also induces VEGF-C-independent activation of VEGFR3 [86], which is, however, antagonized by S1PR1 activity to promote LEC quiescence in lumenized vessels in vivo [54]. By contrast, OSS induces LEC quiescence through upregulation of FOXC2 [40,47], which promotes cell-cell junction integrity and quiescence by restricting TAZ-mediated proliferation [47] as well as MAPK activation [48].…”
Section: Upstream Triggers Of Lec Quiescencementioning
confidence: 99%